2020
DOI: 10.1007/s13364-020-00537-4
|View full text |Cite
|
Sign up to set email alerts
|

Jackal in hide: detection dogs show first success in the quest for golden jackal (Canis aureus) scats

Abstract: Golden jackal (Canis aureus) monitoring in central Europe generates more interest and becomes increasingly important with the species’ appearance in areas where it was previously unestablished. For genetic monitoring of golden jackals via scat collection, the distinction of jackal scats from those of related species such as the red fox (Vulpes vulpes) is crucial: if done incorrectly, it can falsify diet studies or inflate costs of DNA analyses. In this study, we tested the potential benefits of using domestic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 47 publications
0
9
0
1
Order By: Relevance
“…Our best model reliably predicts the distance to the recording AudioMoth up to 400 m. Estimated number of responding animals showed a strong negative relationship with the distance in both considered models, indicating that abundance of golden jackals (at higher distances) might therefore be underestimated in a "realworld" analysis, where the group size of the golden jackal pack is not previously known. Estimation of group size and group composition can be done differently using other passive monitoring applications, like DNA analyses through scats (Hatlauf et al 2021). Nevertheless, we found that our models reliably estimate distances of howling golden jackal packs.…”
Section: Discussionmentioning
confidence: 83%
“…Our best model reliably predicts the distance to the recording AudioMoth up to 400 m. Estimated number of responding animals showed a strong negative relationship with the distance in both considered models, indicating that abundance of golden jackals (at higher distances) might therefore be underestimated in a "realworld" analysis, where the group size of the golden jackal pack is not previously known. Estimation of group size and group composition can be done differently using other passive monitoring applications, like DNA analyses through scats (Hatlauf et al 2021). Nevertheless, we found that our models reliably estimate distances of howling golden jackal packs.…”
Section: Discussionmentioning
confidence: 83%
“…In confirmed golden jackal samples, we amplified 13 unlinked autosomal microsatellite loci as well as two sex markers for individualization and sex determination. All genetic analysis was performed as described in Hatlauf et al 2020.…”
Section: Methodsmentioning
confidence: 99%
“…On three occasions, the study area was also searched with a trained scat detection dog (Hatlauf et al 2020). A total of 8 scats were found.…”
Section: First Proof Of Reproduction 2021mentioning
confidence: 99%
“…Three trained dogs (two Labrador Retriever and one Flat Coated Retriever, all females, and > 2 years of age) and two professional handlers (L. Hollerbach and L. Wirk), all with several years of experience in scat finding and sampling (e.g. Hollerbach et al 2018;Hatlauf et al 2020), searched for wolf scats. Dog 1 and its handler searched for scats in 2018 and in summer 2019.…”
Section: Scat Detection Dogmentioning
confidence: 99%